2013
DOI: 10.1098/rspb.2012.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Motion-guided attention promotes adaptive communications during social navigation

Abstract: Animals are capable of enhanced decision making through cooperation, whereby accurate decisions can occur quickly through decentralized consensus. These interactions often depend upon reliable social cues, which can result in highly coordinated activities in uncertain environments. Yet information within a crowd may be lost in translation, generating confusion and enhancing individual risk. As quantitative data detailing animal social interactions accumulate, the mechanisms enabling individuals to rapidly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…In the rummy nose tetra (Hemigrammus rhodostomus) during collective U-turns [28,35], the analysis of directional correlations between fish suggests that each fish mainly reacts to one or two neighbors at a time [28]. These results are in line with theoretical works that have suggested that, instead of averaging the contributions of a large number of neighbors, as suggested by many models [18-20, 23, 36, 37], individuals could pay attention to only a small number of neighbors [25][26][27][28]38]. This mechanism would overcome the natural cognitive limitation of the amount of information that each individual can handle [39].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the rummy nose tetra (Hemigrammus rhodostomus) during collective U-turns [28,35], the analysis of directional correlations between fish suggests that each fish mainly reacts to one or two neighbors at a time [28]. These results are in line with theoretical works that have suggested that, instead of averaging the contributions of a large number of neighbors, as suggested by many models [18-20, 23, 36, 37], individuals could pay attention to only a small number of neighbors [25][26][27][28]38]. This mechanism would overcome the natural cognitive limitation of the amount of information that each individual can handle [39].…”
Section: Discussionsupporting
confidence: 79%
“…In this species, it has been shown that the transmission of behavior in a school was best described by a model in which the response probability of a fish depends on the fraction of active neighbors perceived by that fish. However, because of the cognitive load that is required for an individual to constantly monitor the movements of a large number of neighbors, it has been suggested that animals may focus their attention on a small subset of their neighbors [25][26][27]. In a previous work, we found experimental evidence that supports this assumption.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…It is explicitly mentioned in some works [6], and implicitly present in a number of models, see, e.g. [7], and the rather complicated escape-pursuit mechanisms introduced in [8,9] to describe marching locusts, or the 'motion guided attention' of [10]. It can even be found in variants of simple flocking models such as the Vicsek model, where local alignment of constantspeed particles competes with noise [22][23][24].…”
mentioning
confidence: 99%